Personal Data Security Violations in East Jakarta Regional Elections: Legal Analysis Through Personal Data Protection Legislation - Khairul Alwan Albaldan; Nin Yasmine Lisasih (Yayasan Kawanad, 2025)
This research examines the personal data breach case during the East Jakarta regional elections and analyzes the legal responsibilities of the General Elections Commission (KPU) from the perspective of Law Number 27 of 2022 concerning Personal Data Protection (PDP Law). Employing a juridical-normative method, statutory-regulatory approach, and conceptual framework, this study investigates the hacking incident involving the Permanent Voters List (DPT) database by a hacker using the pseudonym